Amylase production studies and partial purification of amylolytic enzyme from Enterococcus Faecium DMF78 - Tabanao, Glaiza Lumabi (2008)
The amylolytic enzyme of Enterococcus faecium DMF78 was isolated and partially purified from the fermentation broth. Amylase production and enzyme assay conditions were optimized prior to purification. Amylase production was found to be better at the following cultural conditions: raw sago starch as carbon source and incubation without shaking. The highest productivity of amylases was obtained at the first hour of incubation and generally declined thereafter. Prior to the purification protocol was sequenced as follows: ammonium sulfate precipitation at 90% saturation, dialysis and anion-exchange chromatography (DEAE-cellulose). The partially purified amylase preparation had a purification-fold of 1.57, a recovery of 24.69% and specific activity of 115.31 U/mg. Purity was monitored using SDS-PAGE analysis but distinct protein bands were not observed probably due to very dilute samples